ON THE CONGRUENCE OF THE FORMATION OF METAMORPHOGENIC COMPLEXES OF THE SOROKYNSKA ZONE, GRANODIORITES OF THE OSYPENKIVSKY MASSIF AND THE PEGMATITE NODE OF BALKA KRUTA (AZOV MEGABLOCK OF THE UKRAINIAN SHIELD) - Osmachko, L.S. (Institute of Geological Sciences, NAS of Ukraine, 2020)
Detailed geological-structural studies of the crystalline basement at the boundary of the West Azov anticlinorium and Central Azov synclinorium zones have been carried out, in particular, within the Sorokynska fault zone and the Osypenkivsky massif of granodiorites. It is established that this part of the foundation is a hierarchical, self-similar and highly-coordinated dislocation structure, formed as a result of multi-stage petro-structural transformations. The author directly identified eight generations of dislocation structures, which are indicators of eight stages of structural and material transformations of the studied part of the crystalline basement. Dislocation structures (structural-material neoformations) of the first five generations are formed by mineral paragenesis, which correspond to Р-T conditions from granulite to epidote-amphibolite – green-shale facies of metamorphism. The structural and material neoformations of the fourth and fifth of the defined generations are most intensively developed, being coordinated with the pegmatite bodies. The dislocation structures of the younger generations are mostly formed by the products of fragile destruction, i.e. they are formed under cold conditions and only reinforce the previously formed structural and material inhomogeneity.Data on the structure of the Kruta Balka pegmatite node are systematized according to the principle of hierarchy of geological formations. It is shown that this object is a natural highly-ordered component of the Sorokynska zone, which can only be a consequence of its formation due to the involvement of the entire volume of this zone in multi-stage dislocation transformations. That is, the formation of ore-bearing bodies of the studied zone occurred synchronously with the containing non-metallic geological bodies, in similar geological-dynamic conditions — in several stages of structural/material transformations of the Precambrian basement under shear/rotation deformations. Therefore, the rare-metal mineralization of the studied pegmatite node occupies areas within the zone that are the most structurally and materially differentiated and can be attributed to the type of tectonic-metamorphogenic formations. These facts show that all the filling of the Sorokynska zone together with the glomerum of pegmatites is the united tectonicgeochemical system, which was created at least in seven stages of structural-material transformations of the studied part of the crystalline basement.A schematic model of the multistage formation of the Precambrian structural-material pattern of the central part of the Azov megablock is proposed and the structural positions of ore bodies in this pattern are outlined.